El entrelazamiento de la naturaleza y el artificio: Merleau-Ponty y las filosofías de la physis - García, Esteban Andrés (2006)
“The Intertwining of Nature and Artifice: Merleau-Ponty and the Philosophies ofPhysis”. This paper attempts to delineate the main tenets of Merleau-Ponty’sunderstanding of nature, highlighting particularly the history of the notiondeveloped in Merleau-Ponty’s last courses (La nature]. The analysis covers preSocratic cosmologies, the Aristotelian notion of physis, and the Merleau-pontyaninterpretation of mechanicism and Modern teleology. In the first place, it refersto the critique of the categories with which the physis has been traditionallyunderstood. This critique is founded on the originary adscription of thesecategories to what is humanly instituted and constructed. Secondly, it showsthe limitations of this critique by pointing out that human technique may beinterpreted as an imitation and extension of nature. The evaluation of both sidesof this circular argument gives rise to a particular intertwining (Ineinander)between the natural and the human. It finally discusses Merleau-Ponty’semphasis on the need to recover the original meaning of nature as “ground” and“surplus”.